A Eficácia de programas de educação sobre os conhecimentos relativos à postura sentada e transporte e carregamento de peso em escolares do ensino fundamental de duas 4ª séries de uma escola municipal da cidade de Bauru - Camargo, Isabela Padrenosso Pepe de (2007)
This work had as aim to verify the knowledge changes of concept related to sitting posture and lifting and carrying weight through educations programs comprehending a repetition program managed by the trained teacher and operative games. There were 39 subjects from 4th grade elementary students who participated of the project, both sex, from a municipal school of Bauru. To the achievement of the proposed objective, it was evaluated previous knowledge (M1) of the students concerning the subject. Afterwards was applied a procedure of teaching in both classes (C1 and C2). After finishing this stage, it was accomplished another valuation called intermediary (M2), and thereupon it was applied an operative game program in classroom 1 and an operative game with repetition program managed by the trained teacher in classroom 2. Finally it was accomplished the last stage, the last valuation (M3) about the knowledge of the students concerning the subject. To the mistakes percentage analysis about the theoretical knowledge related to the sitting posture, it was request Friedman test and the comparison between the programs from the answers of the test before and after of the intervention was considered Mann-Whitney test. In comparison between the groups, it has observed than the moments (M1, M2, and M3) did not show significant statistically difference (p>0,05). In comparison with the valuation moments, within each group, there was a significant statistically difference on groups 1 and 2, when it was compared the moment 1 with 3 and the moment 2 with 3. It follows that the educations programs were important to increase the level of the information of the students related to sitting posture.